Pengaruh Pengalaman Merek, Kepercayaan dan Kepuasan dalam Membangun Merek: Loyalitas; Sebuah Penelitian Empiris Tentang Merek Kosmetik Ramah Lingkungan - Pasya Istiara Dhea; Anton Agus Setyawan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study is to analyze the impact of brand experience, brand trust, and brand satisfaction on brand loyalty for environmentally friendly cosmetic products, with a focus on consumers who have purchased and used the product. This research employs a quantitative approach with purposive sampling techniques, involving 200 respondents. Data collection was conducted using a questionnaire that assessed aspects such as brand experience, satisfaction, trust, and brand loyalty. The analysis method used is Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the help of SmartPLS software. The results indicate that brand experience, brand trust, and brand satisfaction have a positive and significant effect on brand loyalty, with a significance value of 0.000 (p < 0.05). These findings provide valuable insights for marketers to strengthen brand loyalty by enhancing positive brand experiences, maintaining product communication transparency, and increasing consumer engagement through social media and loyalty programs.